Polyvinyl alcohol reinforced with crystalline nanocellulose for 3D printing application. (June 2018) - Cataldi, A.; Rigotti, D.; Nguyen, V.D.H.; Pegoretti, A.
Abstract: The aim of this work is to produce fully biodegradable nanocomposite filaments with improved thermo-mechanical properties, to be used in fused deposition modeling (FDM) 3D printing process. At this aim, nanocomposites consisting of poly(vinyl alcohol) (PVOH) containing various amounts (from 2 to 20 wt%) of cellulose nanocrystals (CNC) were produced by solution mixing, grinded and extruded into filaments by a single screw extruder. The obtained nanocomposite filaments were then used to feed a desktop 3D printer. In both filaments and 3D printed specimens, CNC promoted a progressive enhancement of thermal stability manifested in an increase of the glass transition temperature measured by differential scanning calorimetry. Moreover, both dynamic storage and loss moduli were also increased proportionally to the filler content, and a positive reduction of the creep compliance was observed. For a CNC content of 10 wt% the creep compliance at a given loading time (one hour) decreased in both filament (by 47%) and in 3D printed samples (by 35%) in comparison to neat PVOH. Ultimate mechanical properties of filaments also increased with the introduction of CNC till 10 wt%, with a maximum reinforcement effect observed at 2 wt% of CNC for which an increase of 81% in the values of tensile energy to break and 45% in the stress at break were observed. An enhancement in tensile properties was observed also for 3D printed samples at 5 wt% of CNC for which the stress at break manifested an improvement of 73%. Adhesion between layers in 3D printed parts resulted to play a major role in the fracture behavior.